Uji Performa Alat Pengering Tray Dryer Untuk Komoditas Hasil Pertanian Yang Memanfaatkan Kalor Buangan Kondensor Mesin Pengkondisian Udara (Air Conditioning) Domestik - Apollo Apollo; Sonong Sonong; Andi Fathin Faruq R; Rastutu Rastutu (Politeknik Negeri Ujung Pandang, 2023)
The drying methods currently used by farmers still rely heavily on direct solar power, so that the continuity of drying to reduce water content cannot be controlled properly, which has a direct impact on the low quantity and quality of drying results, as well as poor product hygiene. Utilization of condenser waste heat from cooling machines is one of the development applications for heat pump systems. The advantages of heat pumps for the drying process include their ability to control the temperature and humidity in the drying chamber, so that they can be adjusted for various drying conditions and the drying process is more efficient and environmentally friendly. This research aims to determine the performance of drying machines for agricultural commodities (cocoa beans) using the method of developing a domestic air conditioning machine, by adding a condenser arranged in series with the main condenser to function as a drying chamber. The results of the modification of this tool consist of five main parts, namely the compressor, tray dryer room (additional condenser), main condenser, expansion valve, and evaporator. Testing of this dryer was carried out with two types of experiments, namely experiments without load and experiments with load. The test was carried out at the maximum working time of the condenser by setting the lowest working evaporator, namely 16Â°C. The lower the working temperature of the evaporator, the higher the working temperature of condenser 1. This is done to get maximum work from this modified dryer. Based on tests for temperature and relative humidity (RH) under load and no-load conditions, the values are not too different. After approximately 2 hours of operation or when the machine was working in steady state, the highest temperature was obtained at 87Â°C while the highest average RH was obtained at 78% in the drying rack space. The performance of this agricultural commodity drying machine has functioned well, especially for cocoa beans which have been dried to a standard moisture content of 7.5% in accordance with SNI 2322-2008 for an operating time of 130 minutes. The dryer system by utilizing exhaust heat from the condenser in this domestic air conditioning machine can work well without reducing its main function as indicated by the maximum temperature value of 20oC around the evaporator.Â